ANALISYS OF INTERVENTION OF AN ELEMENTARY SCHOOL IN THE PRESENTATION AND RESCUE OF CULTURAL VALUES (Fiep Bulletin - online, 2014)
Knowing that the Physical Education should allow the exercise of different corporal activities, including the ones which came from several cultural manifestations, the aim of this study is to compare the expectation of parents and their children, students of a elementary school in Belo Horizonte, Minas Gerais, about the need of rescuing some cultural values, through playings, games and dances during the Physical Education class. Qualitative questionnaires were tested on students from 1st to 4th grade and their respective parents. As for statistical treatment, it was used descriptive statistics and T tests for non-parametric data, through the statistical package 'Microsoft Excel for Windows'. No significative differences were found (p=0,251955) about students and their parent's satisfaction referring to the content supplied in class. Results showed some divergences on parents expectation when compared to the student's. While students think that Physical education classes are important for intellectual, physical and social development, and that it should offer a good education; parents expect these classes to stimulate cooperation and provide activities such as: games, sports, dances, gymnastics and fights. Parents and students agreed that Physical Education classes have to provide socialization. To end it up, it is concluded that has a predominance of the preference of social values on the cultural ones, for students and parents.
Keywords: culture; lazer; physical education